Viscum coloratum (Komar.) Nakai: A Review of Botany, Phytochemistry, Pharmacology, Pharmacokinetics and Toxicology - Han Di; Congcong Shen; Shengyu Zhang; Yanhong Wang; Feng Guan (Biomolecules)
Viscum coloratum (Komar.) Nakai (V. coloratum) is a traditional Chinese herbal medicine. It is used in treating rheumatism and paralysis, lumbar and knee soreness, weakness of the muscles and bones, excessive leakage of menstruation, leakage of blood in pregnancy, restlessness of the fetus, dizziness and vertigo. All information about V. coloratum was collected through databases such as PubMed, Google Scholar, Web of Science, and the China National Knowledge Infrastructure and supplemented by consulting classical Chinese medical books. To date, 111 compounds have been isolated and identified from V. coloratum, including flavonoids, phenylpropanoids, terpenoids, diarylheptanoids, alkaloids, other components, and macromolecular compounds, such as polysaccharides and lectins. These chemical components exhibit anti-inflammatory, anticancer, antioxidant, and anti-cardiovascular disease effects, among other beneficial effects. According to the reports, alkaloids, lectins, and other chemical components present in V. coloratum may induce toxicity due to excessive intake or accidental ingestion. However, there are few reports on the toxicology of V. coloratum, and there is a lack of studies on the toxicity of V. coloratum with known in vitro or preclinical activity. It is suggested that further studies on the toxicology of V. coloratum should be conducted in the future. In this paper, the botany, traditional uses, phytochemistry, pharmacology, and pharmacokinetics of V. coloratum are summarized, and the progress and shortcomings in toxicology are discussed, so as to provide a possible direction for future research on V. coloratum.